KENDALA DAN PERBAIKAN PENDIDIKAN ISLAM YANG IDEAL - Deri Wanto (Conciencia, 2018)
Every era certainly has a separate challenge. In the development of the Indonesian nation from the old order to the new order era and era to the reform era that seemed to give a very clear feel and color for this nation, especially in the field of education. What has happened? Precisely education in Indonesia to get a new problem, namely the birth of "intersection" policies and "paths of problems" that run until now. Education which is a symbol of the glory and development of the nation-children that must marginalize even more Islamic Education which is part of the institutions under the auspices of the ministry of religion and remain separated in the memories of the ministries of education and culture. This paper is a form of qualitative research library with a sociological approach that sees the history and development of Islamic education at Islamic Religious Higher Education in Indonesia.